AhR and SHP regulate phosphatidylcholine and S-adenosylmethionine levels in the one-carbon cycle - Young-Chae Kim (Nature Communications, 2018)
Methyl metabolites in the one-carbon cycle, such as phosphatidylcholines and S-adenosylmethionine, play a role in hepatic triglyceride regulation. Here Kim et al. show that AhR and SHP are both involved in the expression of several key enzymes of one-carbon metabolism, with the former regulating them early after feeding and the latter inhibiting AhR at later stages.